2021
DOI: 10.2147/ppa.s323766
|View full text |Cite
|
Sign up to set email alerts
|

Improving Adherence to Wearing Compression Stockings for Chronic Venous Insufficiency and Venous Leg Ulcers: A Scoping Review

Abstract: Purpose Patient adherence to wearing compression stockings in the management of chronic venous insufficiency (CVI) and venous leg ulcers (VLUs) is low. Poor adherence with compression stockings contributes to recurrence and impaired healing of VLUs. As such, the purpose of this review was to report on the scientific evidence related to adherence and explore modifiable factors which impact adherence with compression stockings. Methods A systematic search was conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 91 publications
(369 reference statements)
0
25
0
4
Order By: Relevance
“…However, further research on long-term adherence and health care outcomes after implementation of the improvements is necessary. Multidimensional interventions to improve adherence were found the show promising results [34], although further investigations with high-quality trials are required. Some weaknesses of our study have to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, further research on long-term adherence and health care outcomes after implementation of the improvements is necessary. Multidimensional interventions to improve adherence were found the show promising results [34], although further investigations with high-quality trials are required. Some weaknesses of our study have to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Ein Review von Bar et al. berichtet Raten zwischen 20 und 95 %, wobei in den eingeschlossenen Studien teilweise Kriterien wie das Einlösen des MKS-Rezepts und die Durchführung empfohlener Übungen berücksichtigt wurden, die über übliche Adhärenzkriterien hinausgehen [ 42 ].…”
Section: Diskussionunclassified
“…Dabei sollte berücksichtigt werden, dass Patienten bei Interviews und in Studien ihre Adhärenz im Sinne einer sozialen Erwünschtheit ggf. zu positiv darstellen; dies fällt bei einem Abgleich mit Sensordaten auf, die in Studien-Settings in MKS integriert wurden [ 42 , 43 ].…”
Section: Diskussionunclassified
“…Unidimensional interventions that aim to improve behaviors associated with adherence to compression stockings have often been unsuccessful and none have demonstrated consistent superiority over others. 25 In contrast, research into improving adherence in other chronic health conditions including diabetes mellitus 26 and chronic kidney disease, 27 demonstrates more positive impacts from personalized and multidimensional approaches. A recent scoping review 25 of adherence to wearing compression stockings found that, while personalized and multi-dimensional interventions show promise, further high-quality research is required.…”
Section: Introductionmentioning
confidence: 99%
“… 25 In contrast, research into improving adherence in other chronic health conditions including diabetes mellitus 26 and chronic kidney disease, 27 demonstrates more positive impacts from personalized and multidimensional approaches. A recent scoping review 25 of adherence to wearing compression stockings found that, while personalized and multi-dimensional interventions show promise, further high-quality research is required. It recommended that the design of a multidimensional behavior change intervention to improve adherence with compression stockings, must accommodate the multitude of adherence barriers and be sufficiently flexible to deliver tailored personal interventions.…”
Section: Introductionmentioning
confidence: 99%